2007
DOI: 10.1111/j.1742-4658.2007.06144.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the prevention of amyloid fibril formation by α‐crystallin

Abstract: The molecular chaperone, alpha-crystallin, has the ability to prevent the fibrillar aggregation of proteins implicated in human diseases, for example, amyloid beta peptide and alpha-synuclein. In this study, we examine, in detail, two aspects of alpha-crystallin's fibril-suppressing ability: (a) its temperature dependence, and (b) the nature of the aggregating species with which it interacts. First, the efficiency of alpha-crystallin to suppress fibril formation in kappa-casein and alpha-synuclein increases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 53 publications
(107 reference statements)
5
41
0
Order By: Relevance
“…The interaction of αBc with amyloid fibril-forming proteins, e.g. α-synuclein, ataxin-3, apolipoprotein C-II, kappa-casein and β2-microgobulin, is such a situation (Cox et al 2016;Esposito et al 2013;Hatters et al 2001;Rekas et al 2004;Rekas et al 2007;Robertson et al 2010). The variation in sHsp chaperone mechanism depending on conditions and the degree of unfolding of the target protein is consistent with various studies.…”
Section: The N-and C-terminal Flanking Regions In Shspssupporting
confidence: 87%
“…The interaction of αBc with amyloid fibril-forming proteins, e.g. α-synuclein, ataxin-3, apolipoprotein C-II, kappa-casein and β2-microgobulin, is such a situation (Cox et al 2016;Esposito et al 2013;Hatters et al 2001;Rekas et al 2004;Rekas et al 2007;Robertson et al 2010). The variation in sHsp chaperone mechanism depending on conditions and the degree of unfolding of the target protein is consistent with various studies.…”
Section: The N-and C-terminal Flanking Regions In Shspssupporting
confidence: 87%
“…Thus, the design of such studies does not address the effect(s) sHsps have on the latter stages of aggregation, which is as important to consider since, in vivo, levels of sHsps in the cell increase after aggregation has commenced as a result of the activation of the stress response [104,105]. Apart from interacting with monomeric species, sHsps also bind to species formed further along the aggregation pathway, including mature amyloid fibrils [106][107][108][109]. For example, when introduced during the elongation phase of α-synuclein (α-syn) or amyloid- peptide (A aggregation, αBc prevents further fibril growth by binding along the length of mature fibrils, preventing secondary nucleation events that facilitate further fibril growth [106][107][108].…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 99%
“…Apart from interacting with monomeric species, sHsps also bind to species formed further along the aggregation pathway, including mature amyloid fibrils [106][107][108][109]. For example, when introduced during the elongation phase of α-synuclein (α-syn) or amyloid- peptide (A aggregation, αBc prevents further fibril growth by binding along the length of mature fibrils, preventing secondary nucleation events that facilitate further fibril growth [106][107][108]. Our recent work, using apolipoprotein C-II (apoC-II) as a model fibril-forming protein, has shown that, by binding to fibrils, αBc stabilises them, preventing their (dilution-induced) fragmentation, and causes them to associate (tangle) into larger species reminiscent of protein inclusions [109].…”
Section: The Chaperone Mechanism Of Shspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased TFT binding could also potentially result from agglomeration of a-synuclein fibrils, [22] , but such an effect was previously seen in the final stages of the fibrillation process and was preceded by a rapid growth in TFT fluorescence, which was not observed in the presence of PAMAM.…”
Section: Tft Bindingmentioning
confidence: 99%